Pigment Production Using Submerged Fermentation - Mekala Venkatachalam (Fermentation, 2024)
There has been a continuous increase in consumer awareness regarding the availability of natural, sustainable, biodegradable options in all sectors, including food, cosmetics, pharmaceuticals, textiles, painting, printing inks, etc [...]